First report of the parasitoid Hemencyrtus herbertii Ashmead (Hymenoptera: Encyrtidae) in the central region Goiás, Brazil - H. Marchiori, C. (Scientific Journal of Zoology, 2014)
The flies included in the infra-order Muscomorpha have medical and veterinary importance, since they may produce myiasis and act in carrying pathogens to man and animals. They have been found to carry more than 100 species of disease-causing organisms such as bacteria, protozoa and helminthes. As a possibility to control these insects, the natural regulators can be used, such as parasitoids that are the responsible agents for the reduction of the insects pests populations. This paper report the first occurrence of parasitoid Hemencyrtus herbertii Ashmead (Hymenoptera: Encyrtidae) central region of Goiás. The pupae were obtained by the flotation method. They were individually placed in gelatin capsules until the emergence of flies or their parasitoids. Between November 2013 and January 2014, six pupae were obtained from Sarcodexia lambens (Wiedemann) (Diptera: Sarcophagidae) of which were collected two specimens H. herbertii in two pupae. The overall percentage of parasitism was observed in 33.3%. Parasitoids are responsible for reducing the populations of flies that proliferate on various substrates. Evaluation of these species for natural control over these insects is important for enabling studies that aim towards subsequent selection of species for use in biological control programs.